Frequent Occurrence of Faulty Practices, Misconceptions and Lack of Knowledge among Hypothyroid Patients - A Goel; C Shivaprasad; A Kolly; A.A Pulikkal; R Boppana; C.S Dwarakanath (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Hypothyroidism is a common endocrine disorder with a reported prevalence of 4%-10%. Previous studies have reported significant gaps in the basic knowledge about the condition in hypothyroid patients. It has also been observed that faulty practices prevail among these patients. There is paucity of data on the assessment of knowledge and practices among treated hypothyroid patients. Aim: The present study was aims to assess the knowledge, awareness and practices in treated hypothyroid patients. Materials and Methods: The current cross-sectional study was conducted on 244 consecutive hypothyroid patients, attending the Endocrinology Outpatient Department (OPD). The patients were asked to fill a structured questionnaire pertaining to knowledge and practices about various aspects of hypothyroidism. Results: Only two-thirds of the participants correctly identified thyroid as a gland and 41% were aware that hypothyroidism is caused due to decreased function of the thyroid gland. The most common symptom attributed to hypothyroidism was weight gain (139 responses). Nearly 45% of the patients believed alternative forms of medicine can be used for treatment of hypothyroidism. It was believed by 42% of the patients that hypothyroidism runs in the family and about 10% believed it could be transferred to their spouses. Only 33% of the patients gave one hour gap between levothyroxine and food intake. Conclusion: The study demonstrates the lack of knowledge about basic aspects of hypothyroidism among the patients. In addition, there is a high prevalence of misconceptions and faulty practices. The study highlights the need for comprehensive patient education to improve therapeutic outcomes and compliance among hypothyroid patients.